2005
DOI: 10.1097/01.ju.0000181206.16447.e2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction After Radical Prostatectomy: Prevalence, Treatments, Restricted Use of Treatments and Distress

Abstract: Our findings reveal the need to explore broader strategies for improving patient coping ability and adaptation. They also point to the need to explore the role of resumed satisfying sexuality in overall quality of life following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 46 publications
1
68
1
2
Order By: Relevance
“…Studies as well as review articles on this topic that summarize research to date are available in this and other publications. 1,3,5,6,8,9,[11][12][13][14] In spite of the advances toward the restoration of erectile functioning promoted by nerve-sparing surgery, [15][16][17][18] penile rehabilitation 16,[19][20][21][22] and erectogenic aids, 3,11,[23][24][25] satisfaction with erectile dysfunction treatment appears to vary with the particular treatment, and is typically reported not to be high by the men who sought help. 13,26,27 Miller et al 28 reported that only 10% of men were satisfied with their treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies as well as review articles on this topic that summarize research to date are available in this and other publications. 1,3,5,6,8,9,[11][12][13][14] In spite of the advances toward the restoration of erectile functioning promoted by nerve-sparing surgery, [15][16][17][18] penile rehabilitation 16,[19][20][21][22] and erectogenic aids, 3,11,[23][24][25] satisfaction with erectile dysfunction treatment appears to vary with the particular treatment, and is typically reported not to be high by the men who sought help. 13,26,27 Miller et al 28 reported that only 10% of men were satisfied with their treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Men's infrequent pursuit of erectogenic help suggests that other factors in sexual recovery may have a significant role. Psychosocial aspects of sexual recovery are cited in some studies 3,29 and offer an opportunity to examine the context of erectile recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Although surgical removal of the prostate gland is associated with a high 10 year survival rate in localized cases (93%), 34 sexual dysfunction is a common and often enduring side effect of this treatment. [35][36][37] In one major survey, 85% of patients reported experiencing some erectile dysfunction within the last 6 months even 4.3 years after treatment, and 61% reported moderate or extreme distress relating to this dysfunction. 35 Prior work has indicated that psychological interventions directed at psychoeducation or teaching stress management skills can improve aspects of quality of life in men recovering from PCa treatment.…”
Section: Psychological Interventions For Men Recovering From Prostatementioning
confidence: 99%
“…Approximately 85% of men who are started on ADT experience a number of sexual side effects ( Figure 2) of which loss of erections is the single most troublesome 36 in patients who have curative therapy for PCa and the literature demonstrates that both patients and partners are affected negatively by ED. 37,38 Improving QoL can be achieved by improvements in ED which in turn improve sense of masculinity and self-esteem.…”
Section: Sexual Changesmentioning
confidence: 99%